Defining governance in Uganda in a changing world order, 1962-94 - Kintu-Nyago, Crispin (Rhodes University, Faculty of Humanities, Department of Political Studies, 1996)
This study argues that much of early post colonial Uganda's political developments, had its roots in the colonial patterns of governance. It was, however, the imperative of Uganda's early post colonial rulers to have formulated and maintained conditions for legitimate and orderly governance. Largely, this required a coherent political class with a mass based and mobilising political movement, that moreover had a political programme that catered for the interests of its support base. Indeed, their opting to negate these very prerequisite conditions, contributed greatly to Uganda's subsequent political disorder, and it's further marginalisation in the International Political Economy. This study suggests that since the impact of colonialism in Uganda, its governance policies have closely been linked to the broader dictates of the International Political Economy. A reality that the policy makers in post colonial Uganda should have realised, and in the process attempted to advantageously adapt to the Ugandan situation. Their was a qualitative improvement in Uganda's governance from 1986. This study illustrates that this was a result of the emerging into power of a political class, whose policies deliberately and strenuously attempted to fulfil the above mentioned criteria. Their is need to link Uganda's foreign and governance policies. Consequently a conscious and deliberate effort has to made by its policy makers, to ensure that the two are amicably adapted to each other, so as to derive the best possible benefits. For instance what Uganda needs in the existing New World Order are development, domestic and foreign investments and export markets for its produce. All of which can only be obtained if political order through a legitimate political system and government exists. With a leadership, that moreover, deliberately attracts foreign investments and creates the enabling conditions for competitive economic production. The onus is upon Ugandans to ensure that they institutionalise conditions for their appropriate governance and foreign policies. For this thesis argues that the International Political Economy is dynamic, and Uganda was never predestined to be at its margins.
Keywords: Uganda -- Politics and government|Uganda -- Economic conditions|World politics|International relations